The Conspiracist Strategy: Lessons from American Alternative Health Promotions - Gad Yair (European Journal of American Studies)
Hofstadter's classic essay "The Paranoid Style in American Politics" opened a floodgate of analyses of fear and conspiracy theories in American culture. The present paper adds to those studies by providing a cultural interpretation of commercials for alternative cures. It shows that publishers of such commercials often use a "conspiracist strategy" in two interrelated steps. They first raise fears of government collusion with 'Big Pharma.' They then call citizens-cum-patients to protect their liberties from hidden machinations by buying 'hidden' or 'censured' cures. While doing so they employ a series of means to seem professional yet persecuted; scientific though in clandestine. Their graphics and apocalyptic narratives necessitate patients to take swift actions. By manipulating fears and conspiratorial suspicions, entrepreneurs promise suffering 'patriots' that by choosing their alternative cures they would win back their liberty and health. The paper discusses the general theoretical implications for studying conspiracy theories while calling for a comparative approach for observing local habitual predispositions on the one hand, and the culturally adapted conspiracist strategies for manipulating them, on the other hand. In contemporary America, for example, politicians and media outlets employ conspiracist strategies to raise fears from the 'deep state.' They succeed doing so because those conspiracist strategies and the suspicious habitus they manipulate spring from the same democratic source.